Analisis Model Kurikulum Pembelajaran Pendidikan Agama Islam Pasca Pandemi Covid-19 - Syarifah Syarifah; Farida Isroani; Muwahidah Nurhasanah; Samsul Samsul; Khoula Azwary (Sekolah Tinggi Agama Islam Sumatera Medan, 2022)
Education in Indonesia follows the development of the curriculum that has been given by the government. The biggest challenge at the moment is no longer Covid-19, but a new normal that requires adaptability. This study aims to analyze the post-Covid-19 pandemic curriculum model and the supporting and inhibiting factors for its implementation. This research was conducted at MI Nurussalam Ngawi, using qualitative research methods, with a case study approach. Data collection techniques using observation techniques, interviews and documentation studies. The results showed that MI Nurussalam followed the government's mandate to choose one of the three curriculum options provided by the government, namely the 2013 Curriculum, the Emergency Curriculum (simplified 2013 Curriculum), and the Prototype Curriculum. In this case, MI Nurussalam chose to implement the 2013 curriculum, arguing that before the pandemic, this curriculum had already been implemented. The supporting factors for the implementation of the 2013 curriculum during the recovery period are the teacher's role as an indicator of implementing learning, the online learning implementation tools used, fun learning methods. While the inhibiting factors are the lack of cooperation between teachers and parents in guiding online learning, the lack of learning support facilities and infrastructure during the Covid-19 pandemic, the motivation of students in implementing learning at madrasas and at home.